Relationship between visual acuity and visual field and its reproducibility in patients with retinitis pigmentosa - Asaoka, Ryo; Miyata, Manabu; Oishi, Akio; Fujino, Yuri; Murata, Hiroshi; Azuma, Keiko; Obata, Ryo; Inoue, Tatsuya (Eye (London), 2023)
Background/Objectives To investigate the association between visual acuity (VA) and visual field (VF) and its reproducibility in patients with retinitis pigmentosa (RP). Subjects/Methods The study cohort comprised 227 eyes of 227 patients with RP. The reproducibility of two Humphrey VF tests (10-2 Swedish Interactive Threshold Algorithm [SITA] tests) performed within a period of 3 months was calculated using the root mean squared error (RMSE) of each VF test point’s sensitivity. The association between the logarithm of the minimum angle of resolution (logMAR) VA and VF sensitivity was investigated. Additionally, the relationship between RMSE and age, fixation loss, false positives, false negatives, and logMAR VA was determined. Results The association between visual sensitivity and VA was most tight at the fovea, and it became weak toward the peripheral region in an eccentric manner. VF reproducibility appreciably increased as VA decreased. In particular, reproducibility was significantly decreased when logMAR VA was >0.5 compared with logMAR VA ≤ 0. Conclusion Reproducibility of VF tests decreases with a decrease in VA. Careful consideration is necessary when a patient’s logMAR VA is >0.5.